Marketing Da’wah through New Media at the "Teras Dakwah” (Da’wah Terrace) Yogyakarta, Indonesia - Eko Saputra (Jurnal Dakwah Risalah, 2022)
Da'wah today has undergone a significant shift. This article discusses the market religion-based da'wah in the Teras Dakwah in Yogyakarta. This article uses netnographic and ethnographic studies to reveal the da'wah marketing of the Teras Dakwah. The paper finds that the consequences of market religion-based da'wah lead to the fusion of religious authorities, hybrid congregations, and delocalization of religious messages, including place, region, age, culture, language, and ethnicity. Thanks to its media marketing, the Teras Dakwah can freely enter diverse segments of young people across identities. The Teras Dakwah has become a religious entrepreneur. It spreads da’wah that is accepted as pleasure for young people based on considerations of rational choice and economic theory (law of demand and offers). The Teras Dakwah provides a form of da'wah program in a market mechanism that can be enjoyed based on the tastes of young people. The role of the Teras Da’wah media is very significant in the success of the Teras Dakwah religious program. The Teras Dakwah will not successfully reach various segments of young people from cross-religious hybrid identities if it does not use new media channels.